Mahasiswa PAI dan Kitab Kuning - Angga Halomoan; Dini Asfia Dewi; Siti Syakdah; Ikmal Yusuf Nasution (Pusat Riset dan Inovasi Nasional, 2025)
The yellow book is a source of Islamic knowledge that is very important in Islamic religious education, such as in the fields of interpretation, hadith, fiqh, and tasawuf. In the world of Islamic education, Islamic boarding schools are one of the formal education that uses the book as the main reference in finding the material taught. This study aims to find out how students of the Islamic Religious Education (PAI) Masters program at FITK UIN North Sumatra interact with the yellow book. The problems studied are regarding students' understanding of classical sentences, the teaching methods used, and the challenges they face in mastering the yellow book. This study uses qualitative methods, and its analysis techniques are interviews, observations and documentation. The results of the study are a description of the role of the yellow book in Islamic higher education and its contribution to the development of more effective teaching methods. Therefore, it is highly recommended for us to know and understand the contents and meaning of the yellow book, as well as to know the role of the yellow book in the world of education.